Selected problems and risks in designing „long relining” using polyethylene pipes - Kuliczkowski, Andrzej (Instal, 2024)
A synthetic description of the „long relining” technology is provided, as well as information on the basic calculation procedure that allows for the selection of a polyethylene pipe that meets all strength requirements. Information is provided on the required preparatory, assembly and final work. An important part of the article is the inclusion of calculation procedures sometimes omitted in projects using a specific example, which are necessary at the stage of pipe preparation and assembly. Failure to make these calculations may result in pipe failure or a shorter than expected period of operation. A list of risks that may occur in the event of improper preparation of this investment is also provided.
Keywords: design; polyethylene pipes; Relining; trenchless rehabilitation; risk